Relationships between sleep disruptions, health and care responsibilities among mothers of school‐aged children with disabilities. Issue 9 (9th June 2013) - Bourke‐Taylor, Helen; Pallant, Julie F; Law, Mary; Howie, Linsey
Abstract : Aim: Sleep problems are more common among children with disabilities. Mothers are likely to provide night‐time care. Mothers of children with disabilities are known to experience high levels of stress and mental health issues compared with other mothers. Relationships between a child's sleep problems, and chronic maternal sleep interruption and subjective health have not been researched. Method: Cross‐sectional mail‐out survey with follow‐up phone call was used. Instruments included the Short Form 36 version 2 and instruments that measured maternal, child and sleep characteristics. Descriptive statistics examined characteristics of participants and correlation, and Kruskal–Wallis test was used to determine important maternal and child characteristics around sleep issues. Results: All mothers ( n = 152) cared for a school‐aged child with a developmental disability including autism spectrum disorder ( n = 94) and cerebral palsy ( n = 29). Nearly half (49%) of the mothers were awoken more than 4 nights/week. Three distinct sleep groups were identified: no sleep interruption; sleep interruption once/night, 4 nights/week; and more frequent interruption. Mothers experiencing the most sleep interruptions reported significantly poorer health on six Short Form 36 version 2 dimensions. Night‐time caregiving was associated with higher child care needs rather than children's diagnoses. Mothers who experienced more sleep interruption also participated less in health‐promoting activities (active leisure, time with socially supportive others) during the day. Conclusion: This study identifies a group of mothers with chronic sleep interruption and demonstrates related poor maternal subjective health and lower participation in health activities that may service to support maternal health. Mothers with children with the highest daytime care needs also experienced high night‐time care responsibilities. Changes to service provision are recommended to identify mothers in need of additional supports and services.